2013
DOI: 10.1136/emermed-2013-203113.20
|View full text |Cite
|
Sign up to set email alerts
|

Lyrica Nights–recreational Pregabalin Abuse in an Urban Emergency Department

Abstract: Objectives & BackgroundSince ‘legal highs' emerged as drugs of abuse in the UK, Emergency Physicians have battled to keep up with the latest drug craze. Whilst many of these drugs present with recognisable toxidromes, the effect of new compounds or medications cannot be readily predicted. In Belfast, we have witnessed a recent increase in the number of patients presenting after recreational abuse of Pregabalin (Lyrica). Patients, state that the medication induces a state similar to drunkenness, hence the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…Euphoria was already described in pre-marketing studies [29]. ''Real-life'' experience revealed that it was used in order to potentiate the effects of methadone [28], or for drunkenness-like effects (''Budweiser's'' effect) [27]. Furthermore, drug-dependent patients are at risk of pregabalin dependence, as it is sometimes used off-label to help drug discontinuation, for instance discontinuation of benzodiazepines [31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Euphoria was already described in pre-marketing studies [29]. ''Real-life'' experience revealed that it was used in order to potentiate the effects of methadone [28], or for drunkenness-like effects (''Budweiser's'' effect) [27]. Furthermore, drug-dependent patients are at risk of pregabalin dependence, as it is sometimes used off-label to help drug discontinuation, for instance discontinuation of benzodiazepines [31].…”
Section: Discussionmentioning
confidence: 98%
“…The disproportionality analysis found no significant association between pregabalin or amitriptyline and abuse or dependence, whereas this association was significant with clonazepam. From now on, there is strong evidence highlighting the abuse potential of pregabalin in the real-life setting [9,[24][25][26][27][28][29][30]. Several psychoactive effects of pregabalin explain the risk of recreational misuse and thus its abuse and dependence potential.…”
Section: Discussionmentioning
confidence: 99%
“…In one case series [ 37 ], sixty percent of patients presented to the ED with seizures and 20 % required ICU admission. Plasma, serum or blood concentrations of pregabalin may be measured to monitor therapy or to confi rm a diagnosis of poisoning in hospitalised patients.…”
Section: Acute Drug Abusementioning
confidence: 98%
“…Intubation and ventilation were required in 2 patients while seizures were observed in 6 patients (26). GABAergic effect and stimulant properties of pregabalin are considered to play a role in the abuse of the drug (27).…”
Section: Discussionmentioning
confidence: 99%